THE STRATEGIC, MILITARY AND COUNTERINSURGENCYTACTICS OF THE PERMESTA MOVEMENT (CASE STUDY GUERILLA WARFARE IN SULAWESI) - Elfira Sylviani Kaunang; Fauzia G. Cempaka T; Muhammad Hadianto; Sigit Purwanto (Bajang Institute, 2024)
The urgency of the PERMESTA movement lies in its expression of regional dissatisfaction with the centralization of power and economic injustice after Indonesia's independence. The move highlights the need for a more equitable redistribution of resources, regional autonomy, as well as showing how the involvement of foreign powers can complicate domestic conflicts, triggering a government military response. The purpose of the study is to analyze The Strategic, Military and CounterinsurgencyTactics of the PERMESTA Movement (Case Study Guerilla Warfare in Sulawesi). The method used is qualitative descriptive with a systematic Literature Review approach. The results of this study show that the Permesta movement in the 1950s showed how regional dissatisfaction with political and economic centralization could trigger rebellions. Permesta, which began in Sulawesi, emphasizes the demand for regional autonomy in response to the perceived development inequality between the central and regional governments. Using guerrilla warfare tactics, the movement leveraged the geographical terrain and local support to fight the government. On the other hand, the Indonesian government implements a counter-insurgency strategy that combines military operations and efforts to win the hearts of the people through socio-economic development. This conflict shows the importance of local community support in determining the success of the insurgency movement or government response. Although the government has succeeded in quelling the rebellion, the Permesta case highlights the challenges in dealing with regional conflicts involving complex political, ideological, and socio-economic dynamics in an archipelagic country like Indonesia.